PENINGKATAN KEMAMPUAN MENENDANG DENGAN KAKI BAGIAN DALAM PERMAINAN SEPAKBOLA MELALUI VARIASI LATIHAN - Maidalina Maidalina (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2019)
The problem in this study is the low willingness of students to take part in learning soccer games so that most students do not master the basic techniques of playing football, especially in kicking with the inner leg, of 20 students only around 35% - 45% who are able to kick with the inner leg is good and the rest still have not reached the minimum classical completeness that has been determined which is 77, besides that many students pay less attention when the teacher explains the technical material in the game of football. The purpose of this study was to improve the ability to kick with the inner leg of a student's soccer game. The results showed that the average value of the ability of students before the cycle was categorized as quite competent with the percentage of completeness 70.82% (35.00%, complete 7 people). In the first cycle kicking with the inner leg using a variety of exercises the average ability of students increases with the competent category with the percentage of completeness 77.48% (60.00%, complete 12 people), it shows that students like the variety of exercises taught by the teacher, but the value the average has not reached the specified completeness which is 80%. While in the second cycle the average ability of students was categorized as competent with a percentage of completeness of 87.13% (90.00%, completed 18 people) which showed that classical completeness had been achieved which was determined in this study, namely 80%. This means that the method of effective training variations to improve the ability to kick with the inner leg of the football game of class V-B even semester SDN 004 Teratak Buluh.